2015
DOI: 10.1186/s13023-015-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovation by patients with rare diseases and chronic needs

Abstract: We provide the first empirical exploration of disease-related innovation by patients and their caregivers. Our aims were to explore to what degree do patients develop innovative solutions; how many of these are unique developments; and do these solutions have positive perceived impact on the patients’ overall quality of life? In addition, we explored the factors associated with patient innovation development, and sharing of the solutions that the patients developed.MethodsWe administered a questionnaire via te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…Thus, a study of a sample of medical patients in Portugal shows a much higher fraction innovating to serve their own needs (53% vs. the typical range of 2–8%) (14). The 500 patients surveyed are coping with chronic diseases ranging from rare genetic disorders such as Angelman's Syndrome to more common but very serious chronic diseases like Type 1 diabetes.…”
Section: Health-related Innovation By the Public/users In The Househomentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a study of a sample of medical patients in Portugal shows a much higher fraction innovating to serve their own needs (53% vs. the typical range of 2–8%) (14). The 500 patients surveyed are coping with chronic diseases ranging from rare genetic disorders such as Angelman's Syndrome to more common but very serious chronic diseases like Type 1 diabetes.…”
Section: Health-related Innovation By the Public/users In The Househomentioning
confidence: 99%
“…The Oliveira et al (14) Portuguese patient innovation study does not assess diffusion effort as a function of perceived general value of an innovation. However, it does report that a significant proportion of the 263 patients and caregivers who reported solutions, also reported investing efforts to share their solutions with others (32%, n = 84).…”
Section: Health-related Innovation By the Public/users In The Househomentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated that 8% of the solutions developed by patients with rare diseases and their caregivers were novel to medicine 6. There are plenty of e-patients all over the world.…”
Section: E-patients Using Their Initiativementioning
confidence: 99%
“…Oliveira et al suggest that when patients develop innovations, these are mostly used to help themselves, or those they care directly for, but are rarely shared more widely. They surveyed 500 patients who had rare diseases to measure how many had developed innovations to help themselves and/or support their own care.…”
Section: Introductionmentioning
confidence: 99%